Admissible Relation on Plus Weighted Finite State Mealy Machine - Dr. K. CHITRA (Utilitas Mathematica, 2025)
The major goal of this work is to introduce the admissible(weak admissible, strong admissible) relation on the set of Plus Weighted Finite State Mealy Machine (pwfmm).